PYOGENIC GRANULOMAS IN THE ORAL CAVITY: A SERIES OF CASES - Deyan Z. Neychev; Radka B. Cholakova; Tanya I. Sbirkova; Stanimir N. Kisselov; Svitlana Y. Bachurska; Dimitar T. Atanasov (Peytchinski Publishing, 2019)
Introduction: Pyogenic granulomas represent tumour-like lesions affecting the skin and the oral cavity. This classic definition can be somewhat misleading because such lesion is not associated with infection and lacks any clinical evidence of pus or histological evidence of actual granulation tissue. Scientific literature sources estimate its prevalence to 1:25000 per capita, affecting females twice as often. Pyogenic granuloma in the oral cavity affects the interdental papilla in 70% of the cases. Purpose: The authors present a case series of pyogenic granulomas in the oral cavity with varying localization and therapeutic approach. Materials and methods: This article presents six clinical cases of PG. Diagnosis is challenging due to similarities with a number of tumorous and non-tumorous neoplasms (formations) in the oral cavity. Two histological types of pyogenic granuloma can be identified: lobular and non-lobular capillary hemangioma. Surgical excision is the treatment method of choice, followed by deep curettage of the lesion toward the underlying bone. Such precautions are necessary because 15,8% of the lesions tend to recur over time. Results: Alternative therapeutic approaches for removal of PG are explored, which are aimed at reducing the recurrences after surgical treatment. Such an opportunity is provided by utilization of Er:Yag laser because its effect can reach the underlying bone. Conclusion: Pyogenic granuloma represents a diagnostic challenge, specifically in cases of atypical localization. The effective surgical approach requires complete removal of the pathological process from the surrounding healthy structures in order to prevent recurrences.